A 4-Day Incubation Period of Plasmodium falciparum Infection in a Nonimmune Patient in Ghana: A Case Report. (17th January 2019) - Orish, Verner; Afutu, Leslie; Ayodele, Oladapo; Likaj, Lorena; Marinkovic, Aleksandra; Sanyaolu, Adekunle
Abstract: Plasmodium falciparum can cause severe infection and has the shortest incubation period compared with all the other Plasmodium species. Incubation periods of 9–14 days for the immune and 6–14 days for the nonimmune have been reported for P. falciparum . However, an incubation period of less than 5 days has not been reported, as of yet. This report presents a case of a 23-year-old nonimmune female who presented with signs and symptoms 4 days after being bitten by mosquitoes while visiting Ghana. The patient was successfully treated with a 1-day course of parenteral artesunate, followed by a 3-day course of oral artemisinin combination therapy.